2009
DOI: 10.1002/adsc.200900056
|View full text |Cite
|
Sign up to set email alerts
|

Cyclobutenes as Isolable Intermediates in the Gold(I)‐Catalysed Cycloisomerisation of 1,8‐Enynes

Abstract: Abstract:The gold(I)-catalysed isomerisation of 1,8-enynes allows the efficient synthesis of functionalised bicycloA C H T U N G T R E N N U N G [5.2.0]nonenes. Notably, these cyclobutenes derivatives can be isolated as reactive intermediates that could undergo subsequent gold(I)-catalysed transformations such as isomerisation, fragmentation or ene reaction to furnish more structurally complex products. This study also provides useful information related to the mechanism leading to metathesis-type derivatives,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
50
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(52 citation statements)
references
References 51 publications
(3 reference statements)
0
50
0
2
Order By: Relevance
“…20 Although the bicyclo[5.2.0]nona-1(9),2-diene 32, obtained by gold(I)-catalyzed [2 þ 2] cycloaddition of a 1,6-dien-8-ynes, was stable in CD 2 Cl 2 , it slowly underwent ring opening in CDCl 3 due to a trace amount of HCl present in this solvent (Scheme 15). 21 The silyl ether 33, which was synthesized from cyclobutenedione monoethylenedithioketal, underwent ring opening with outward rotation of the siloxy group at 50 1C to give diene 34 (Scheme 16). 22 The subsequent Diels-Alder reaction of 34 with The ring opening of cyclobutenes bearing unsaturated groups provides an opportunity for the synthesis of ring-expanded carbocycles by subsequent electrocyclic reactions.…”
Section: Cyclobutene Ring Openingmentioning
confidence: 99%
“…20 Although the bicyclo[5.2.0]nona-1(9),2-diene 32, obtained by gold(I)-catalyzed [2 þ 2] cycloaddition of a 1,6-dien-8-ynes, was stable in CD 2 Cl 2 , it slowly underwent ring opening in CDCl 3 due to a trace amount of HCl present in this solvent (Scheme 15). 21 The silyl ether 33, which was synthesized from cyclobutenedione monoethylenedithioketal, underwent ring opening with outward rotation of the siloxy group at 50 1C to give diene 34 (Scheme 16). 22 The subsequent Diels-Alder reaction of 34 with The ring opening of cyclobutenes bearing unsaturated groups provides an opportunity for the synthesis of ring-expanded carbocycles by subsequent electrocyclic reactions.…”
Section: Cyclobutene Ring Openingmentioning
confidence: 99%
“…On the other hand, gold catalysis has been applied successfully to transformations that are traditionally carried out with carbene systems [135][136][137][138]. In this regard, it should be noted that the widespread formation of cyclopropanes, which is frequently invoked as an indication of the carbene character of the reactive intermediate species, in the reaction between activated alkynes and alkenes, can also occur in a stepwise, nonconcerted fashion via charged intermediates [139].…”
Section: Structure Of M-alkyne and M-alkene Reactant Complexesmentioning
confidence: 99%
“…The formation of cyclobutenes has been investigated in the presence of various electrophilic complexes, both in the case of 1,n-enynes [70,[133][134][135][136][137], and 1,7enynamides [138][139][140][141] (Scheme 35). This formal [2 þ 2]-cycloaddition allowed, for example, the cyclization of enyne 172 to tricyclic alkene 173 in the presence of 10 mol% of gallium chloride [133].…”
Section: Bicyclobutene Formationmentioning
confidence: 99%
“…[3,4] However, construction of such systems with medium-ring parent frameworks is highly challenging due to high entropy costs in the cyclization and/or transannular interactions within the products. [6] Later, Inagaki and co-workers reported similar gold catalysis with a boron-containing "Z-type ligand." [6] Later, Inagaki and co-workers reported similar gold catalysis with a boron-containing "Z-type ligand."…”
mentioning
confidence: 99%
“…[6,7] We confirmed that the catalysts with L1 and L2, having triarylsilyl and triarylmethyl end caps, respectively, caused much more rapid reactions of 1 (2 mol% Au, rt in 0.02 M of CH 2 Cl 2 ) than the previously reported systems [ Table 1, 0.25 h (entries 1 and 2) vs. 24 h (entries 3 and 4)], giving 7exo-dig-cyclization-isomerization products 2-4 in good-to-high yields. [6,7] We confirmed that the catalysts with L1 and L2, having triarylsilyl and triarylmethyl end caps, respectively, caused much more rapid reactions of 1 (2 mol% Au, rt in 0.02 M of CH 2 Cl 2 ) than the previously reported systems [ Table 1, 0.25 h (entries 1 and 2) vs. 24 h (entries 3 and 4)], giving 7exo-dig-cyclization-isomerization products 2-4 in good-to-high yields.…”
mentioning
confidence: 99%